Inscribed Athenian laws and decrees in the age of Demosthenes - Lambert, S. D., 1960- (Brill Studies in Greek and Roman Epigraphy, 2018)
This book collects twelve papers which make original contributions to the historical interpretation of inscribed Athenian laws and decrees, with a core focus on significant historical shapes and patterns implicit in the corpus of the age of Demosthenes. Following a synthetic Introduction, two chapters analyse locations and selectivity of inscribing, four explore the implications of the inscriptions for Athenian policy and for developing attitudes to the past, three for aspects of Athenian democracy. The volume concludes with two studies of specific inscriptions. Some of the papers have appeared elsewhere in conference proceedings and Festschriften, some are published here for the first time. The volume complements the author's previous collection, Inscribed Athenian Laws and Decrees 352/1-322/1 BC: Epigraphical Essays .